Knowledge in the 21st Century: Perspective of Buddhism - Chaisuk พระครูปภากรวิหารกิจ ปภากโร; กิตฺติญาโณ พระครูกิตติญาณวิสิฐ (Journal of Educational Review Faculty of Education in MCU, 2018)
Knowledge in the 21st century is rational coherent. In the Life of the Buddha and his disciples’ lives, the start, search and methods of learning were complied with the knowledge required in the 21st century. Creative thinking, problem solving, leadership, knowledge searching and career-oriented knowledge not against the laws and regulations are called ‘The Middle Way Knowledge’. According to Buddhism, learning for changing the life is to go deep in that field with the clear focus. Learning for changing oneself starts from study to practice evaluation by oneself respectively. The results of knowledge are used to develop oneself, community and society to certify that the results of knowledge are qualified and beneficial.